DISTRIBUTION NETWORK PLANNING WATER PIPE IN THE DISTRICT OF PEACE VILLAGE Besiq DISTRICT WEST KUTAI. - HERMAWAN, WAHYU (KURVA S JURNAL MAHASISWA, 2014)
Clean water is one of the major needs for human survival , the need for bathing , cooking, drinking , etc. However, of the many water contained in the earth is only 3 % in the form of freshwater contained in rivers , lakes , and groundwater.The distribution system strongly supports continuity of flow to the water service in a town , village or settlement population. Concomitant with population growth that resulted also increase demand for water . Shortcomings in terms of quantity , quality and continuity of clean water will lead to life becomes uncomfortable.Some of the problems that arise in meeting the needs of clean water is clean water distribution system to the residential quarters smooth. For not overcome it needed clean water distribution network that is well and able to serve the needs of clean water to residents in the area.So that in the area in the village of Besiq will be Pipelines Distribution Plan for Clean Water . In order to serve the purpose distribution in the village for 10 years.